Mixed communities gentrification by stealth? - Bridge, Gary; Butler, Tim 1949-; Lees, Loretta (The Policy Press, 2012)
"Encouraging neighbourhood social mix has been a major goal of urban policy and planning in a number of different countries. This book draws together a range of case studies by international experts to assess the impacts of social mix policies and the degree to which they might represent gentrification by stealth. The contributions consider the range of social mix initiatives in different countries across the globe and their relationship to wider social, economic and urban change. The book combines understandings of social mix from the perspectives of researchers, policy makers and planners and the residents of the communities themselves. Mixed Communities also draws out more general lessons from these international comparisons - theoretically, empirically and for urban policy. It will be highly relevant for urban researchers and students, policy makers and practitioners alike"--Provided by publisher
Keywords: Social Integration; Embourgeoisement (Urbanisme); Intégration sociale; Bevölkerungsstruktur; gentrification; Gentrification; Gentrifizierung; Kommunalpolitik; PSYCHOLOGY; Social integration; SOCIAL SCIENCE; Electronic books; Aufsatzsammlung